Ancient Genomes Reveal the Evolutionary History and Origin of Cashmere-Producing Goats in China. (23rd April 2020) - Cai, Yudong; Fu, Weiwei; Cai, Dawei; Heller, Rasmus; Zheng, Zhuqing; Wen, Jia; Li, Hui; Wang, Xiaolong; Alshawi, Akil; Sun, Zhouyong; Zhu, Siqi; Wang, Juan; et al.
Abstract: Goats are one of the most widespread farmed animals across the world; however, their migration route to East Asia and local evolutionary history remain poorly understood. Here, we sequenced 27 ancient Chinese goat genomes dating from the Late Neolithic period to the Iron Age. We found close genetic affinities between ancient and modern Chinese goats, demonstrating their genetic continuity. We found that Chinese goats originated from the eastern regions around the Fertile Crescent, and we estimated that the ancestors of Chinese goats diverged from this population in the Chalcolithic period. Modern Chinese goats were divided into a northern and a southern group, coinciding with the most prominent climatic division in China, and two genes related to hair follicle development, FGF5 and EDA2R, were highly divergent between these populations. We identified a likely causal de novo deletion near FGF5 in northern Chinese goats that increased to high frequency over time, whereas EDA2R harbored standing variation dating to the Neolithic. Our findings add to our understanding of the genetic composition and local evolutionary process of Chinese goats.